An Investigation of TNT Equivalence of Hemispherical PE4 Charges - RIGBY, Samuel E.; SIELICKI, Piotr W. (Engineering Transactions, 2014)
The TNT equivalence of an explosive is given as the equivalent mass of TNT required to produce a blast wave of equal magnitude to that produced by a unit weight of the explosive in question. Currently, there is a lack of agreement in the literature on the TNT equivalence (TNTeq) of PE4. This paper presents a combined numerical and experimental investigation of TNTeq for hemispherical PE4 charges in far-field blast events. Experimental results are compared to a series of numerical analyses conducted with different masses of TNT explosive and conclusions are drawn in order to provide a more informed value of TNTeq. It is found that a TNTeq of 1.2 best describes the blast waves produced from PE4 detonations, and this factor is found to be invariant of the distance from the explosive when considering far-field events.